2018
DOI: 10.1111/jvh.12998
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on models of care effectiveness and barriers to Hepatitis C treatment in prison settings in the EU/EEA

Abstract: Hepatitis C prevalence in prison populations is much higher than in the community. Effective hepatitis C treatment within this population does not only have a direct individual health benefit, but may lead to substantial community dividend. We reviewed available evidence on hepatitis C treatment in prison settings, with a focus on the European Union/European Economic Area. A systematic review of the literature (PubMed, EMBASE, Cochrane library) was performed and complemented with searches for conference abstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…Evidence surrounding prison-based HCV care interventions in the DAA era is scarce (37). High treatment uptake and completion achieved in our study indicates the great willingness towards treatment among people with HCV in prisons; these outcomes are comparable with another DAA-based prison study from Italy (38).…”
Section: Hcv Treatment Uptake and Completionsupporting
confidence: 73%
“…Evidence surrounding prison-based HCV care interventions in the DAA era is scarce (37). High treatment uptake and completion achieved in our study indicates the great willingness towards treatment among people with HCV in prisons; these outcomes are comparable with another DAA-based prison study from Italy (38).…”
Section: Hcv Treatment Uptake and Completionsupporting
confidence: 73%
“…The reasons identified for low rates of linkage and treatment uptake included refusals, short sentences and prison transfers -all in keeping with other studies and representing unique challenges for HCV care in prison settings. 23,24 To improve HCV screening at the Établissement de détention de Montréal and other Canadian provincial prisons, systematic opt-out screening should be considered. 5 Admission to any correctional facility provides an important public health opportunity to identify cases of chronic HCV infection through screening, and, as all subsequent cascade steps are dependent on this initial step, implementing systematic screening at admission and during incarceration is imperative.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of the effectiveness of MoCs for HCV in European prisons found that seven studies utilizing second‐generation DAAs in France, Italy and Spain achieved SVR rates of 85%–98%, and one study that switched from interferon therapy to DAA therapy increased SVR rates from 62%–68% to 90%–98% . A Spanish study demonstrated that HCV elimination is possible in a prison setting.…”
Section: Wherementioning
confidence: 99%